Fremanezumab for preventive treatment of migraine: Functional status on headache-free days. (18th September 2018) - VanderPluym, Juliana; Dodick, David W.; Lipton, Richard B.; Ma, Yuju; Loupe, Pippa S.; Bigal, Marcelo E.
Abstract : Objective: To evaluate the effect of fremanezumab on the functional status on headache-free days in phase 2 episodic migraine (EM) and chronic migraine (CM) studies. Methods: Functional status data were collected prospectively via the electronic headache diary on all headache-free days by patients answering questions regarding work/school/household chore performance, speed of work completion, concentration, and feeling of fatigue. Individuals with EM receiving monthly doses of fremanezumab 225 mg (n = 96) or 675 mg (n = 97) or placebo (n = 104) were compared. Individuals with CM receiving fremanezumab 675 mg followed by monthly 225 mg (n = 88) and 900 mg (n = 86) were also independently compared to those receiving placebo (n = 89). Results: In patients with EM, compared to patients receiving placebo, those receiving fremanezumab experienced an increased number of headache-free days with normal function in work/school/household chore performance and concentration/mental fatigue measures compared to their baseline over the entire treatment period (all p < 0.005). An increased number of headache-free days with normal functional performance for some measures was also found in the CM group in those treated with fremanezumab. Conclusion: There was an increased number of headache-free days with normal functional performance on all measures for the patients with EM and some measures for patients with CM in the fremanezumab-treated groups. Further research is required to confirm these findings in a prospective study and to clarify the underlying mechanism(s). ClinicalTrials.gov identifier: NCT02025556 and NCT02021773. Classification of evidence: This study provides Class II evidence that for patients with migraine, fremanezumab increases normal functional performance on headache-free days.